Consumer Perception of Artificial Intelligence-Based Advertising and Its Impact on Purchase Intention: Evidence from an Academic Environment - IMAS PERMATASARI; ANDRIANSYAH BARI; VIVIN WULANDARI (Jurnal Ilmu Manajemen, 2026)
Artificial Intelligence (AI) is rapidly changing the way businesses create and deliver digital advertisements. While AI makes advertising more personalized and visually engaging, consumers do not always respond to AI-generated content in the same way. This study examines how four dimensions of consumer perception influence purchase intention toward AI-based advertising. Using a quantitative approach, data were collected from 120 members of the academic community at Politeknik Negeri Sriwijaya and analyzed using Smart-PLS. The results indicate that attractiveness, credibility, and trust significantly encourage purchase intention, with trust emerging as the strongest predictor. In contrast, authenticity does not significantly influence consumers' intention to purchase. These findings suggest that digitally literate consumers are becoming more pragmatic, placing greater value on useful, credible, and trustworthy advertising than on whether the content is created by humans or AI. The study extends current knowledge on AI-based advertising and offers practical insights for businesses seeking to develop AI-driven advertising strategies that build consumer trust and strengthen purchase intention.